2022
DOI: 10.1159/000519716
|View full text |Cite
|
Sign up to set email alerts
|

Enlarged Vertebral Venous Plexus Alleviated Intracranial Hypertension-Related Symptoms in Patients with Bilateral Transverse Sinus Stenosis

Abstract: <b><i>Background:</i></b> Enlarged vertebral venous plexus (EVVP) was often observed in patients with bilateral transverse sinus stenosis (BTSS). The purpose of this study was to investigate the physiological role of EVVP in BTSS patients. <b><i>Methods:</i></b> Forty-five BTSS patients and 92 normal controls were prospectively recruited from January 2014 to December 2019. The index of transverse sinus stenosis (ITSS) was used for the assessment of BTSS severity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…It has been reported that BTSS is correlated with IH (3). Results from our previous study also supported this finding (6). A triad of IH which manifested as headache, tinnitus, and papilledema are confirmed as the most common symptoms in patients with BTSS in this study.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…It has been reported that BTSS is correlated with IH (3). Results from our previous study also supported this finding (6). A triad of IH which manifested as headache, tinnitus, and papilledema are confirmed as the most common symptoms in patients with BTSS in this study.…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, the presence of EVVP would guarantee sufficient cerebral venous reflux. Our previous report has demonstrated that EVVP compensates for the elevated ICP in patients with BTSS ( 6 ).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations